High-fidelity digital recording and playback sphygmomanometry system. Issue 5 (October 2015) - Lee, Jongshill; Chee, Youngjoon; Kim, Inyoung; Karpettas, Nikos; Kollias, Anastasios; Atkins, Neil; Stergiou, George S.; O'Brien, Eoin
<x xml:space="preserve">Abstract</x> Objectives This study describes the development of a new digital sphygmocorder (DS-II), which allows the digital recording and playback of the Korotkoff sounds, together with cuff pressure waveform, and its performance in a pilot validation study. Materials and methods A condenser microphone and stethoscope head detect Korotkoff sounds and an electronic chip, dedicated to audio-signal processing, is used to record high-quality sounds. Systolic and diastolic blood pressure (SBP/DBP) are determined from the recorded signals with an automatic beat detection algorithm that displays the cuff pressure at each beat on the monitor. Recordings of Korotkoff sounds, with the cuff pressure waveforms, and the simultaneous on-site assessments of SBP/DBP were performed during 100 measurements in 10 individuals. The observers reassessed the recorded signals to verify their accuracy and differences were calculated. Results The features of the high-fidelity DS-II, the technical specifications and the assessment procedures utilizing the playback software are described. Interobserver absolute differences (mean±SD) in measurements were 0.7±1.1/1.3±1.3 mmHg (SBP/DBP) with a mercury sphygmomanometer and 0.3±0.9/0.8±1.2 mmHg with the DS-II. The absolute DS-II mercury sphygmomanometer differences were 1.3±1.9/1.5±1.3 mmHg (SBP/DBP). Conclusion The high-fidelity DS-II device presents satisfactory agreement with simultaneous measurements of blood pressure with a mercury sphygmomanometer. The device will be a valuable methodology for validating new blood pressure measurement technologies and devices.